(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
Viroids are infectious pathogens that affect only plants. Viroids are subviral, being smaller than viruses and possess circular strands of ribonucleic acids (RNAs) with no protein coating. Hunger is a painful sensation for energy caused by depletion of dietary energy. We get this energy, either directly after we eat or from the stored food as glycogen or from that stored as fat. The key objectives of this study are: ►to demonstrate the fact that the nature’s spectacular Controlled Experiment of Naked Genome is the only automatic molecular machine that synthesizes all genomic-things & itself using sunlight-energy (autotrophs) or usable chemical energy-containing nutritive substances including minerals as raw materials in the organism’s compatible environment, ►to verify that Genome’s designed/coded directives are implemented in the synthesis (reproduction including growth, or replication) by its transcripts & proteins that perform as engineers, and ►to prove that viroids are certainly genomic-things by fitting into the definition of genomic-things and to impart the cause of hunger together with the energy intake. Each of the micrographs or evidential videos in the Figures listed or displayed has been devised to be the target and addressive finding (Result) of this study. Viroids are certainly genomic-things. The painful sensation of hunger is for immediate intake of usable chemical energy found in food but not for stomach-fillingness of food mass.